The Blockade of Glutamate N-methyl-D-aspartate Receptors into the Prelimbic of Prefrontal Cortex Decreases Morphine-induced Conditioned Place Preference in Rat - Samad Javadi; Hojjatallah Alaei; Ebrahim Hosseini; Mohammad Amin Edalatmanesh (The Indonesian Biomedical Journal, 2017)
BACKGROUND: The prelimbic area (PL) of the prefrontal cortex is susceptible to abnormal developmental stimuli that raises the risk of addiction. Glutamate receptors play a key role in opiate reinforcement and reward functions in this area. Therefore, we examined the effect of the DL-2-amino-5-phosphonopentanoic acid (AP5), as N-methyl-D-aspartate (NMDA) receptor antagonist into the PL on the phases of conditioned place preference (CPP) induced by morphine.METHODS: Male Wistar rats were divided into 12 groups (3 surgical groups for each dose of morphine in any phase of CPP) and anaesthetized with chloral hydrate. Cannula was implanted into the PL and the AP5 was injected into this area and morphine-induced CPP was investigated. Data were processed with the commercially available SPSS 22 software using one-way ANOVA and Tukey's test. p<0.05 were considered statistically significant.RESULTS: Our findings indicated, morphine in doses of 2.5 to 10 mg/kg induced CPP. Microinjection of various doses of the AP5 into the PL before the administration of the effective dose of morphine significantly reduced place preference in the acquisition and the expression phases of the CPP test compared to the sham group (p<0.001). In another set of our experiments was seen that, different doses of the AP5 with the ineffective dose of morphine only reduced the expression phase of the CPP (p<0.001) while, produced neither preference nor aversion effect on the acquisition phase (p=0.147).CONCLUSION: It seems that the glutamate NMDA receptors in the PL through memory formation and morphine-related reward signals play a critical role in addiction process during morphine-induced CPP.KEYWORDS: N-methyl-aspartate, morphine, glutamate receptor, prefrontal cortex, reward